The Isolation Rate of Escherichia coli 0157:H7 in Toronto and Surrounding Communities - Andrew E Simor; Christine Watt; Donald E Low (Canadian Journal of Infectious Diseases)
Verocytotoxin-producing strains of Escherichia coli, most often serotype 0157:H7, have been associated with both sporadic and epidemic diarrheal disease in Canada. In order to determine the isolation rate of E coli 0157:H7 in outpatients with diarrhea, all stool specimens submitted for culture to Med-Chem Laboratories in Metropolitan Toronto between June 1988 and September 1989 were cultured on MacConkey-Sorbitol agar in addition to standard enteric media. A total of 46 (0.3%) of 16,125 stool specimens yielded E coli 0157:H7 or verotoxin-producing E coli 0157:H−. These isolates came from 31 patients with diarrhea; only 16 (52%) had a history of hemorrhagic colitis and one patient developed hemolytic uremic syndrome. Although MacConkey-Sorbitol agar was useful as a differential medium for detecting E coli 0157:H7, 14.5% of all specimens yielded nonsorbitol-fermenting isolates. It is not certain whether the routine use of MacConkey-Sorbitol agar is justified when isolation rates of E coli 0157:117 are very low.